Strain‐Enhanced Metallic Intermixing in Shape‐Controlled Multilayered Core–Shell Nanostructures: Toward Shaped Intermetallics. (16th April 2020) - Williams, Benjamin P.; Young, Allison P.; Andoni, Ilektra; Han, Yong; Lo, Wei‐Shang; Golden, Matthew; Yang, Jane; Lyu, Lian‐Ming; Kuo, Chun‐Hong; Evans, James W.; Huang, Wenyu; Tsung, Chia‐Kuang
Abstract: Controlling the surface composition of shaped bimetallic nanoparticles could offer precise tunability of geometric and electronic surface structure for new nanocatalysts. To achieve this goal, a platform for studying the intermixing process in a shaped nanoparticle was designed, using multilayered Pd‐Ni‐Pt core–shell nanocubes as precursors. Under mild conditions, the intermixing between Ni and Pt could be tuned by changing layer thickness and number, triggering intermixing while preserving nanoparticle shape. Intermixing of the two metals is monitored using transmission electron microscopy. The surface structure evolution is characterized using electrochemical methanol oxidation. DFT calculations suggest that the low‐temperature mixing is enhanced by shorter diffusion lengths and strain introduced by the layered structure. The platform and insights presented are an advance toward the realization of shape‐controlled multimetallic nanoparticles tailored to each potential application. Abstract : Pd‐Ni‐Pt in the mix : A method for studying the intermixing process in a shaped nanoparticle was devised. It uses multilayered Pd‐Ni‐Pt core–shell nanocubes as precursors. Under mild conditions, the intermixing between Ni and Pt could be tuned by changing layer thickness and number, triggering intermixing while preserving nanoparticle shape.